A calibration method for failure modeling in clinching process simulations - Böhnke, Max; Bielak, Christian Roman; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Meschut, Gerson; Steinmann, Paul (Materials Research Proceedings, 2023)
In the numerical simulation of mechanical joining technologies such as clinching, the material modeling of the joining parts is of major importance. This includes modeling the damage and failure behavior of the materials in accordance with varying occurring stress states. This paper presents a calibration method of three different fracture models. The calibration of the models is done by use of experimental data from a modified punch test, tensile test and bulge test in order to map the occurring stress states from clinching processes and to precisely model the resulting failure behavior. Experimental investigations were carried out for an aluminum alloy EN AW-6014 in temper T4 and compared with the simulative results generated in LS-DYNA. The comparison of force-displacement curves and failure initiation shows that the Hosford–Coulomb model predicts the failure behavior for the material used and the tests applied with the best accuracy.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Clinching; Damage; Failure